Le renouvellement du répertoire attique par emprunts - Anne Tichit (Frontière·s)
Using the development of the 6th century B.C. Attic cups as a case study, this paper explores some of the ceramic styles borrowed by the potters from outside the borders of Attica. The example of Attica undoubtedly reveals a broader creative process during the archaic period and illustrates the abundance of inspiration sources. The development of the stemmed foot shape, the creation process of new types or the renewal of the iconographic repertoire of these cups allow us to consider the various modes of influence that nourished the work of the Attic potters. Whether discrete or evident, over a long or short period, the stylistics borrowings are a creative driving force of renewal. The possible vectors of those exchanges are also considered, including the case of itinerant or emigrant potters.